2011
DOI: 10.1073/pnas.1013855108
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive dysfunction and prefrontal synaptic abnormalities in a mouse model of fragile X syndrome

Abstract: Among the hallmark phenotypes reported in individuals with fragile X syndrome (FXS) are deficits in attentional function, inhibitory control, and cognitive flexibility, a set of cognitive skills thought to be associated with the prefrontal cortex (PFC). However, despite substantial clinical research into these core deficits, the PFC has received surprisingly little attention in preclinical research, particularly in animal models of FXS. In this study, we sought to investigate the molecular, cellular, and behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(119 citation statements)
references
References 42 publications
(47 reference statements)
8
107
1
Order By: Relevance
“…However, in contrast to Zalfa et al (2003), another study reported reduced Arc/Arg3.1 protein levels in the orbital frontal cortex and medial prefrontal cortex of FXS mice (Krueger et al, 2011). Future experiments are needed to analyze whether FMRP regulates specific target mRNAs differently depending on the brain region.…”
Section: Increased and Protein Synthesis-independent Mglu 1/5 Ltd In Fxsmentioning
confidence: 98%
See 2 more Smart Citations
“…However, in contrast to Zalfa et al (2003), another study reported reduced Arc/Arg3.1 protein levels in the orbital frontal cortex and medial prefrontal cortex of FXS mice (Krueger et al, 2011). Future experiments are needed to analyze whether FMRP regulates specific target mRNAs differently depending on the brain region.…”
Section: Increased and Protein Synthesis-independent Mglu 1/5 Ltd In Fxsmentioning
confidence: 98%
“…Interestingly, a recent report has shown that prefrontal cortex-dependent forms of learning are altered in Fmr1 KO mice (Krueger et al, 2011), and patients with FXS are specifically impaired in several prefrontal cortex-dependent cognitive skills (Hoeft et al, 2007;Reiss and Hall, 2007;Mercaldo et al, 2009). This suggests that behavioral paradigms testing prefrontal cortical function in Fmr1 KO mice might be a better tool to assess therapeutic strategies for their potential to rescue cognitive impairment in FXS (Krueger et al, 2011).…”
Section: The Behavioral Phenotype Of Fmr1 Mouse Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, patients with FXS are mostly impaired in higher cognition, behavioral flexibility, and inhibitory control, which depend on the prefrontal cortex. To date, very few studies have reported defects in prefrontal cortex-dependent higherorder cognition in Fmr1 KO mice [215,237]. A recent study showed that defects in higher cognition in FXS mouse models were rescued by genetic reduction of the PI3K catalytic subunit p110β in the prefrontal cortex [237].…”
Section: Behavioral and Cognitive Phenotypes In The Fxs Mouse Modelmentioning
confidence: 99%
“…In light of clinical FXS symptomology (i.e., its comorbidity with ADHD), Fmr1 KO mice were evaluated in the five-choice serial reaction time task, considered the gold standard task for attention and impulsivity in rodents (118). Although Fmr1 KO mice were impaired in select phases of a visual-spatial discrimination task, they did not differ from wildtype controls in the five-choice serial reaction time task (119,120). Specifically, Krueger and colleagues found that Fmr1 KO mice took longer to reach criterion during the As a negative regulator of mRNA translation, FMRP influences protein synthesis and can therefore affect the synaptic components located in dendritic spines.…”
Section: Attention and Hyperactivitymentioning
confidence: 99%